Google Form-assisted Consumer Service Quality Instrument: Exploration Factor Analysis (EFA) - Bakti Setyadi; Sulaiman Helmi (International Journal of Artificial Intelligence Research, 2023)
The aim of this article is to use exploratory factor analysis to create a consumer service quality instrument with the help of google form that meets the criteria of valid, reliable, and high fit model. This is a quantitative study that the survey method. A cross-sectional survey was used as the research design. The study's sample size was 200 people who were chosen at random using a simple random sampling technique. A consumer service quality questionnaire was used as the instrument. This instrument was analyzed using Exploratory Factor Analysis techniques. The results revealed that the customer service quality instrument model based on the EFA analysis was already in the fit criteria, that each item had a loading factor greater than 0.05 in addition to item A1, and that the instrument indicator items were declared valid in general. According to the results of the reliability test, the instrument is in the very reliable category.